Wages, Nonwage Job Characteristics and the Search Behavior of Employees - van Ophem, Hans (The Review of Economics and Statistics, 1991)
This paper analyzes the search decision of employees empirically. A maximum likelihood model consisting of a wage equation and a search equation, in which the difference between the present and the nonobserved alternative (market) wage is included, is estimated to investigate the importance of nonwage job characteristics and future wage prospects relative to the present wage. The estimation results indicate that both present and future wages and nonwage job characteristics have a significant impact on the search decisions of employees. Copyright 1991 by MIT Press.